2004
DOI: 10.1063/1.1773931
|View full text |Cite
|
Sign up to set email alerts
|

Die-upset hybrid Pr–Fe–B nanocomposite magnets

Abstract: Anisotropic nanocomposite R–Fe–B/Fe magnets (R=Pr, Tb) were synthesized by hot pressing and subsequent die upsetting blends of R-rich and R-lean melt-spun ribbons. The magnets have a layered structure, in which alternating layers of the two starting alloys lay perpendicularly to the pressing direction. A crystallographic alignment of the R2Fe14B grains is observed in the R-rich layers, whose microstructure is identical to that of the conventional die-upset magnets. The R-lean layers consisting of exchange-coup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…The magnetic alignment indicated by the Mr(//)/Mr(?Þ ratio appears to increase with increasing the deformation rate (height reduction). Microstructural study [1,2] showed that a texture was developed only in the R-rich Nd 2 Fe 14 B single phase alloy region in the die-upset hybrid magnet (Fig. 4).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The magnetic alignment indicated by the Mr(//)/Mr(?Þ ratio appears to increase with increasing the deformation rate (height reduction). Microstructural study [1,2] showed that a texture was developed only in the R-rich Nd 2 Fe 14 B single phase alloy region in the die-upset hybrid magnet (Fig. 4).…”
Section: Resultsmentioning
confidence: 97%
“…The hybrid magnet consisting of the Nd 2 Fe 14 B single phase alloy (called R-rich alloy, hereafter) and the Nd 2 Fe 14 B=Fe nanocomposite alloy (called R-lean alloy) is of interest [1,2]. The hybrid magnet can exploit the merits of the single phase alloy and the nanocomposite alloy: the Nd 2 Fe 14 B single phase alloy guarantees high coercivity and the nanocomposite alloy provides high magnetization.…”
Section: Introductionmentioning
confidence: 99%
“…The anisotropic nature in the die-upset hybrid magnet is probably due to the texture developed in the Nd 13.5 Fe 80 Ga 0.5 B 6 alloy region during the deformation. It has been reported [5] that in the hybrid magnet a texture was developed only in the Nd 2 Fe 14 B single phase region. The magnetic alignment in the die-upset hybrid magnet appears to be inferior to that of the single alloy counterpart.…”
Section: Experimentalsmentioning
confidence: 97%
“…Most of the current nanocomposite materials are virtually isotropic without magnetic alignment. Recently, a unique magnet processing technique, in which the R 2 Fe 14 B/a-Fe nanocomposite (R ¼ Nd, Pr) material was hybridized with Nd 2 Fe 14 B single phase material, was suggested [5,6]. The aim of the present study is to examine the anisotropic nature of the hybrid magnets.…”
Section: Introductionmentioning
confidence: 97%
“…However, a challenge still exists to successfully create these in an anisotropic form. Attempts at die-upset [66,67], thick film synthesis [68], chemical deposition [69], hot extrusion [70], and surfactant-assisted high energy ball milling [50] have all been attempted with very limited success. In each case, either the spacing is insufficiently small or the processing route is no longer viable with the alloy.…”
Section: At General Motors Researchmentioning
confidence: 99%